Multi-omics analysis revealed promoting mechanism of gut derived cellulose-degrading bacteria from Tenebrio molitor on bioconversion of lignocellulosic waste - Xinrui Mao; Wenbiao Jin; Jiaming Li (Bioresource Technology Reports, 2026)

Investigation of CO2 absorption and desorption performance and mechanism of aqueous [TETAH][Im] in a PTFE hollow fiber membrane contactor - Chunyun Zhou; Yanbin Yun; Chang Li; Jia Liu; Jiaming Mao; Wenjuan Yang; Haiyan Huang; Guoqiang Zhuang; Meng Li (Journal of Environmental Chemical Engineering, 2026)

Ionic liquid-modulated Co/Ni heterostructure MOF nanoflower for efficient electrochemical conversion from HMF to FDCA - Shucan Qin; Weizhen Kong; Anshuang Wu; Longmei Shi; Yuhui Ci; Yunqian Ma; Na Wang; Jiaming Mao (Journal of Environmental Chemical Engineering, 2026)

Transport modeling of ZVI-AC mixtures in Cr(VI) remediation driven by spectral induced polarization - Xinmin Ma; Alexis Maineult; Jiaming Zhang; Chen Chao; Ruijue Zhao; Jian Meng; Yaxun Wang; Deqiang Mao (Journal of Hazardous Materials, 2026)

Chlorocholine chloride delays progenitor Leydig cell differentiation via PI3K/AKT pathway activation in rats - Haoran Zhang; Yijia Li; Xiaoxia Wang; Chenping Kang; Qiong Zhang; Defeng Liu; Jiaming Mao; Qianqian Xiao; Weidong Hao (Toxicology, 2026)

Monitoring contaminant removal during in situ chemical oxidation using cross-borehole resistivity tomography and hydrogeology - Teng Xia; Jiaming Zhang; Ruijue Zhao; Miao Li; Shupeng Li; Lili Guo; Deqiang Mao (Journal of Hydrology, 2026)

Ionic liquid-derived fluorine doped high entropy metal oxides as efficient electrocatalysts for sulfion valorization - Longmei Shi; Anshuang Wu; Shengyun Xu; Jinbiao Liang; Shucan Qin; Jiaming Mao; Yanrong Liu; Yunqian Ma (Journal of Environmental Chemical Engineering, 2025)

MKAIS: A Hybrid Mamba–KAN Neural Network for Vessel Trajectory Prediction - Caiquan Xiong; Jiaming Li; Yuzhe Zhuang; Xinyun Wu; Mao Luo; Qi Wang (Journal of Marine Science and Engineering, 2025)
Vessel trajectory prediction (VTP) plays a critical role in maritime safety and intelligent navigation. Existing methods struggle to simultaneously capture long-term dependencies and nonlinear dynamic patterns in vessel movements. To address this challenge, we propose MKAIS, a novel trajectory prediction model that integrates the selective state space modeling capability of Mamba with the strong nonlinear representation power of Kolmogorov–Arnold Networks (KAN). Specifically, we design a feature-separated embedding strategy for AIS inputs (longitude, latitude, speed over ground, course over ground), followed by an MKAN module that jointly models global temporal dependencies and nonlinear dynamics. Experiments on the public ct_dma dataset demonstrate that MKAIS outperforms state-of-the-art baselines (LSTM, Transformer, TrAISformer, Mamba), achieving up to 16.65% improvement in the Haversine distance over 3 h prediction horizons. These results highlight the effectiveness and robustness of MKAIS for both short-term and long-term vessel trajectory prediction.

Lipid-mediated photoprotection confers strong light resilience in hyperaccumulator Sedum alfredii - Yanjiao Dai; Jin Chen; Yang Mao; Huidan Jiang; Wenwen Zhao; Jing Peng; Ruibing Li; Ying Wang; Purui Guo; Mengnan Zhang; Chao Zhang; Jiaming Li; et al. (Plant Science, 2025)

A performance improving method of preparing nonlinear conductive coating for HVDC insulator based on plasma treatment technology: For lower-additive amounts and higher adhesive stability - Zijun Pan; Jiaming Cheng; Quanyou Nie; Zirui Wu; Yujie Qiu; Yuhan Ye; Shiyi Mao; Pu Han; Cheng Pan; Ju Tang (Chemical Engineering Journal, 2025)

Integrated multi-omics reveals mechanistic impact of gut microbiota inhibition on lignocellulose biodegradation in Tenebrio molitor - Xinrui Mao; Jiaming Li; Wenbiao Jin; Wei Han (Bioresource Technology, 2025)

Towards efficient in situ gas thermal desorption remediation assisted with cross-borehole resistivity tomography - Teng Xia; Jiaming Zhang; Miao Li; Shupeng Li; Lili Guo; Peng Liu; Dixiang Wang; Deqiang Mao (Water Research, 2025)

Enhanced carbon dioxide capture via amphiphobic PVDF membrane modification for membrane contactors: Overcoming wettability challenges - Chang Li; Yanbin Yun; Fengguang Huang; Jiaming Mao; Jia Liu; Wenjuan Yang; Chunyun Zhou; Meng Li (Chemical Engineering Journal, 2025)

Anhydrous deep eutectic solvents-based biphasic absorbents for efficient CO2 capture: Unravelling the critical role of hydrogen bond-mediated electron transfer - Jiaming Mao; Yunqian Ma; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Chunyun Zhou; Hongwei Xie; Yanbin Yun (Chemical Engineering Journal, 2025)

A NH2-UiO-66-TiO2/Al2O3 hollow ceramic membrane with an enhanced photocatalytic oxidation performance of NO - Wenjuan Yang; Wenli Liu; Yuanbo Song; Yangyang Wang; Yanbin Yun; Guicheng Liu; Chang Li; Jiaming Mao; Jia Liu; Meng Li; Chunyun Zhou; Manxiang Wang; et al. (Journal of Environmental Chemical Engineering, 2025)

Evolution of in-situ thermal-enhanced oxidative remediation monitored by induced polarization tomography - Teng Xia; Jiaming Zhang; Miao Li; Damien Jougnot; Kai Yang; Shupeng Li; Deqiang Mao (Journal of Hydrology, 2025)

Tracking Cr(VI) removal with spectral induced polarization under ZVI and AC synergetic remediation - Xinmin Ma; Jiaming Zhang; Chen Chao; Shiliang Liu; Khalil Ur Rahman; Shupeng Li; Lili Guo; Deqiang Mao (Environmental Research, 2025)

Experimental and theoretical investigation of an ionic liquid-based biphasic solvent for post-combustion CO2 Capture: Breaking through the “Trade-off” effect of viscosity and loading - Jiaming Mao; Yuhui Ci; Jia Liu; Chang Li; Wenjuan Yang; Yanbin Yun; Guicheng Liu; Meng Li; Manxiang Wang (Chemical Engineering Journal, 2024)

Construction, characterization, antioxidant activity and effects on properties in vitro digestion of selenium nanoparticles decorated with Cyperus esculentus polysaccharides - Chuang Zhai; Yicun Lin; Chunling Mao; Xinxin Li; Ran Zhang; Jiaming Liu; Ling Zhang (Food Bioscience, 2024)

Responses of physiological, microbiome and lipid metabolism to lignocellulose wastes in gut of yellow mealworm (Tenebrio molitor) - Xinrui Mao; Jiaming Li; Enqing Meng; Wenbiao Jin; Wei Han (Bioresource Technology, 2024)

Image-guided structure-constrained inversion of electrical resistivity data for improving contaminations characterization - Xinmin Ma; Jieyi Zhou; Jing Li; Jiaming Zhang; Chunmei Han; Lili Guo; Shupeng Li; Deqiang Mao (Computers & Geosciences, 2024)

Biphasic solvents based on dual-functionalized ionic liquid for enhanced post-combustion CO2 capture and corrosion inhibition during the absorption process - Jiaming Mao; Chang Li; Yanbin Yun; Jia Liu; Wenjuan Yang; Meng Li; Lihua Wang; Chunli Li; Wenli Liu (Chemical Engineering Journal, 2024)

Performance and response of coupled microbial fuel cells for enhanced anaerobic treatment of azo dye wastewater with simultaneous recovery of electrical energy - Liming Hu; Na Liu; Chang Li; Jiaming Mao; Meng Li; Yanbin Yun; Wenli Liu (Environmental Science and Pollution Research, 2023)

Magnetic field assisted process for preparing anti-biofouling PVDF membranes incorporated by hydrophilic magnetic palygorskite - Hengyang Mao; Jiayun Zhu; Shouyong Zhou; Jiaming Wang; Mengting Li; Ailian Xue; Meisheng Li; Yijiang Zhao; Wenbo Peng; Weihong Xing (Applied Clay Science, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Histone deacetylase CsHDA6 mediates the regulated formation of the anti-insect metabolite α-farnesene in tea (Camellia sinensis) - Shuhua Wu; Yuhua Yang; Jiaming Chen; Jianlong Li; Guotai Jian; Jie Yang; Kaiquan Mao; Lanting Zeng; Dachuan Gu (Plant Science, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Expression and Selection of Human Foxm1c Binding Peptides and Their Inhibitions on MCF7 Cancer Cells - Jian Cui; Jiaming Huang; Tailin Guo; Fang Wu; Zhijuan Liang; Lili Xiong; Tingting Huang; Li Zeng; Na Liu; Canquan Mao (International Journal of Peptide Research and Therapeutics, 2014)